IMAJI SUFISTIK ALAM DAN BINATANG DALAM PUISI-PUISI ABDUL HADI W.M., SUTARDJI CALZOUM BACHRI, DAN KUNTOWIJOYO - Sujarwoko, Sujarwoko (ATAVISME, 2020)
Puisi sufistik sebagai abstraksi kehidupan dunia sufi dapat digunakan untuk melihat jatuh bangunnya seorang sufi dalam pendakian rohani. Untuk melukiskan pendakian rohani, puisi sufistik menggunakan imaji alam dan binatang. Tujuan penelitian ini adalah mengungkapkan makna dan mendeskripsikan imaji sufistik alam dan binatang dalam puisi-puisi Abdul Hadi W.M., Sutardji Calzoum Bachri, dan Kuntowijoyo. Penelitian ini menggunakan teori estetika sufistik puisi Braginsky dan metode deskriptif kualitatif dengan data karya-karya ketiga penyair tersebut. Hasil penelitian menunjukkan puisi sufistik karya ketiga penyair tersebut menggunakan berbagai imaji alam: cahaya, gelombang, batu, rumput, pohon, dan angin. Imaji binatang yang digunakan, meliputi: kupu-kupu, kucing, cengkerik, gajah, semut, dan singa. Imaji sufistik alam sebagai sarana untuk menggambarkan kedekatan dan penyatuan diri dengan Tuhan, sedangkan imaji sufistik binatang untuk melukiskan hakikat salik dan liku-liku perjalanan rohani yang dialami pejalan yang sedang mengalami hambatan dan ancaman dalam upaya menuju keindahan rohani sebagai puncak keriangan spiritual.[Natural and Animal Sufistic Images in Abdul Hadi W.M., Sutardji Calzoum Bachri, and Kuntowijoyo Poetries] Sufistic poetry as an abstraction of sufi?s life can be used to see the rise and fall of a sufi in spiritual ascent. To describe spiritual ascent, sufistic poetry uses natural and animals images. The purposed of this research were to reveal the meaning and describe the sufistic images of nature and animal s in Abdul Hadi W.M., Sutardji Calzoum Bachri, and Kuntowijoyo poetries. This research used the sufistic poetry aesthetic theory of Braginsky and qualitative descriptive methods with data on the works of the three poets. The results of the research showed that the poetic works of the three poets used a variety of natural images: light, waves, stone, grass, trees, and wind. Animals imagesthat were used includ: butterflies, cats, cloves, elephants, ants, and lions. Natural sufistic images as a means to describe closeness and union with God, while sufistic imagery of animals were used to describe the nature of salik and the intricacies of the spiritual journey experienced by travelers who were experiencing obstacles and threats in an effort to reach spiritual beauty as the peak of spiritual joy.Keywords: sufistic poetry; sufistic images; natural sufistic images; animals? sufistic images